INTERACTION OF CROSSES AND STOCKING DENSITY ON BREEDING OF Clarias Gariepinus FROM THREE ECO-REGIONS IN NIGERIA: RIVER NIGER (N), RIVER BENUE (B) AND RIVER HADEJIA (H) - Kabir, Hassan Y.; Abubakar, Garba A.; Ikenga, Esther.E.; Mukoro, Juliana E.; Abdul-Azeez, H; Rafindadi, Halimatu .A; Galambi, Abubakar Y. (FUDMA Journal of Sciences, 2026)
This study determined the Interaction of crosses and stocking density on breeding of C. gariepinus from three eco-regions in Nigeria: River Niger (N), River Benue (B) and River hadejia (H). Interaction of cross and stocking density was significant (p
Keywords: Fish; stocking density; breeding of C. gariepinus; River Niger (N); River Benue (B); River Hadejia (H)